Implementación de un manual de seguridad y salud ocupacional en la fábrica de helados Sam Rey ubicada en el cantón Salcedo. - Barragan Yugsi, Diego Estalin (2023)
This research project is based on the design and implementation of an Occupational Safety and Health manual at the Sam-Rey ice cream factory, located in the Salcedo canton, Cotopaxi province, the current situation of the factory was analyzed through the application of an interview to Mr. Manager, surveys of workers and an observation guide in which thematic axes were raised such as: use of personal protection equipment that is provided by the company to workers, training for personnel where learned that the company does not carry out frequently, but relatively rarely, small safety talks, little or no signage at the different jobs, as well as prohibition, obligation and information signs that allow workers to know about the existing dangers, order and cleaning that is maintained by a policy of shifts and schedules for each worker, improvement of working conditions where it is mentioned that ergonomic risks are the ones that most affect 57.15% of the personnel, followed by the electrical risk caused by the wrong placement of the freezing pool and the industrial blender connected to the same power source, and physical risks with 28.57% caused mainly by slippery floor since the surface is covered with pure cement mix. The development and implementation of the Occupational Health and Safety manual have established guidelines and safety standards to guarantee the safety of workers and protect their physical and psychological well-being. The objective is to maintain zero accidents and promote training in accident and disease prevention. In addition, employees are provided with the necessary resources to carry out assigned tasks effectively. The proposed hypothesis, which establishes that preparing and implementing an Industrial Safety and Occupational Health Manual can prevent accidents at the Sam-Rey ice cream factory in the Salcedo canton, Cotopaxi province, was thoroughly examined and verified.